The villa, once beloved - Manibo, Victor (Kensington Publishing, 2025)
"Villa Sepulveda is a storied relic of the Philippines' past: a Spanish colonial manor, its moldering stonework filled with centuries-old heirlooms, nestled in a remote coconut plantation. When their patriarch dies mysteriously, his far-flung family returns to their ancestral home. Filipino-American student Adrian Sepulveda invites hiscollege girlfriend, Sophie, a transracial adoptee who knows little about her own Filipino heritage, to the funeral of a man who was entwined with the history of the country itself. Sophie soon learns that there is more to the Sepulvedas than a grand tradition of political and entrepreneurial success. Adrian's relatives clash viciously amid grief, confusion, and questions about the family curse that theirmatriarch refuses to answer. When a landslide traps them all in thevilla, secrets begin to emerge, revealing sins both intimately personal and unthinkably public. Sifting through fact, folklore, and fiction, Sophie finds herself at the center of a reckoning. Did a mythical demon really kill Adrian's grandfather? How complicit are the Sepulvedas in the country's oppressive history? As a series of ill omens befall the villa, Sophie must decide whom to trust--and whom to flee--before the family's true legacy comes to take its revenge..."--